Geographic spread and inter-annual evolution of populations of Trioza erytreae in the Iberian Peninsula - Arenas-Arenas, Francisco J.; Durán-Vila, Núria; Quinto, Javier; Hervalejo, Aurea (Springer, 2019)
Trioza erytreae per se is a major citrus pest, although its destructive power is much greater as a vector of the non-culturable bacterium ‘Candidatus Liberibacter africanus’ causing the most devastating disease of citrus worldwide: the citrus huanglongbing (HLB). Following early detections of T. erytreae in mainland Europe, simultaneously in Portugal and Spain in 2014, its distributional range has rapidly increased, thus becoming a serious threat to the entire Mediterranean citrus industry. In 2018, one year after our latest survey, the situation has only worsened, with T. erytreae being around 200 km closer to key citrus growing areas in southern Portugal and Spain. Once T. erytreae invades a new area, the degree of severity of its attacks increases very quickly, which is indicative of its potential for invasiveness. We highlight that T. erytreae is currently spread and well established along the northwestern coast of the Iberian Peninsula, ranging from Cedeira in A Coruña (Spain) to Pontes/Setúbal in Portugal, covering approximately 600 km on a straight uninterrupted line. Implementation of further containment and control measures are critical to addressing this growing risk.